The Fine Art of Writing a Message: RNA Metabolism in the Shaping and Remodeling of the Nervous System - Landínez-Macías, María; Urwyler, Olivier (Frontiers in Molecular Neuroscience, 2021)
Neuronal morphogenesis, integration into circuits and remodeling of synaptic connections occur in temporally and spatially defined steps. Accordingly, the expression of proteins and specific protein isoforms that contribute to these processes must be controlled quantitatively in time and space. A wide variety of post-transcriptional regulatory mechanisms, which act on pre-mRNA and mRNA molecules, contributes to this control. They are thereby critically involved in physiological and pathophysiological nervous system development, function and maintenance. Here, we review recent findings on how mRNA metabolism contributes to neuronal development, from neural stem cell maintenance to synapse specification, with a particular focus on axon growth, guidance, branching, and synapse formation. We emphasize the role of RNA-binding proteins, and highlight their emerging roles in the poorly understood molecular processes of RNA editing, alternative polyadenylation and temporal control of splicing, while also discussing alternative splicing, RNA localization and local translation. We illustrate with the example of the evolutionary conserved Musashi protein family how individual RNA-binding proteins are on the one hand acting in different processes of RNA metabolism, and on the other hand impacting multiple steps in neuronal development and circuit formation. Finally, we provide links to diseases that have been associated with malfunction of RNA-binding proteins and disrupted post-transcriptional regulation.